Respostas oferecidas pela efetuação para a superação de crises no empreendedorismo de estilo de vida - Borsatto, Fabiano Serra (2024)
This research presents a study on how seven lifestyle entrepreneurs located in the state of São Paulo overcame a crisis from the perspective of effectuation. The objective of this thesis was to explain how effectuation contributes to overcoming a crisis for lifestyle entrepreneurs. In the field of entrepreneurship, lifestyle entrepreneurs distinguish themselves from classic or Schumpeterian entrepreneurs by prioritizing the maintenance or pursuit of a desired new lifestyle over the maximization of financial returns and accumulation of material goods. The pursuit of a balance between personal and professional life and the professionalization of passions are also characteristics observed in this type of entrepreneur. The identity of the lifestyle entrepreneur, combined with their network of relationships and knowledge about the enjoyable activity they decided to pursue, creates a close link between this type of entrepreneur and effectuation. Effectuation is a concept in the field of entrepreneurship that helps explain how entrepreneurs identify and exploit new opportunities using their available means (identity, knowledge, and network of relationships) to venture. In a crisis situation, where resources are scarce and there is often no time for predictive actions to face and overcome it, effectuation, as an entrepreneurial action, seems to be a viable and applicable path for the entrepreneur, as it is expected that the entrepreneur will identify new opportunities and take initiatives to overcome the crisis in this turbulent environment. The research adopted a qualitative approach, using in- depth semi-structured interviews, due to its descriptive/explanatory nature compatible with the inductivism necessary to access contextual aspects that are little or never studied before. The collected data were transcribed and analyzed with the help of the qualitative data analysis software Atlas-ti. The data extracted from the studied cases were analyzed both individually and comparatively, seeking to find similarities, contrasts, and emerging insights, offering valid results from the cases selected for convenience and snowball. As a result, the research reveals that effectual logic provides more effective means to overcome a crisis and, at the same time, provides evidence of how lifestyle entrepreneurs associate entrepreneurial techniques and tactics to face and overcome crises. In addition to answering the research question, we present two significant and unprecedented findings in the literature. The first finding refers to the persistence of these entrepreneurs in continuing their ventures in crisis contexts, which is nurtured by their identity. The second finding refers to the formation of networks of solidarity and reciprocity that aim not only at overcoming the crisis of the venture but also at maintaining and preserving the environment that sustains and promotes the lifestyle.